Revision of species of the genus Tephritis Latreille 1804 (Diptera: Tephritidae) with entire apical spot - Korneyev, Severyn V. (Zootaxa, 2013)
Eleven species of the genus Tephritis with an uncommon banded wing pattern and/or solid apical crossband/spot instead of apical fork, mainly from the Palaearctic Middle East, are described and keyed, including Tephritis afrostriata new species, T. cameo new species, T. gladius new species, T. ochroptera new species, and T. robusta new species. The following synonymy is established: Tephritis admissa Hering 1961 = T. conflata Dirlbek & Dirlbek 1995 new synonym. Lectotypes for T. angulatofasciata Portschinsky 1892 and T. tatarica Portschinsky 1892 are designated. New distribution records are reported. Tephritis tatarica is recorded to be reared Alfredia nivea Kar. et Kir.; T. admissa, T. cameo, T. gladius, and T. ochroptera were swept from Cousinia spp., which very probably are their host plants.